The Israeli Palestinians : an Arab minority in the Jewish state - Bligh, Alexander, 1949- (Cass series--Israeli history, politics, and society., 2003)
One of the most crucial issues to affect national policy in the state of Israel is that of relations between its Jewish and Arab citizens. This edited collection offers a comprehensive analysis of the most significant factors to have contributed to current conditions.